What Could be Achieved with Greater Public Hospital Autonomy? Comparison of Public and PNFP Hospitals in Uganda - Ssengooba, Freddie; Atuyambe, Lynn; Mcpake, Barbara; Hanson, Kara; Okuonzi, Sam (The International Journal of Management Research and Practice, 2002)
The policy of hospital autonomy has been discussed for some time in Uganda. There is little evidence from Uganda or elsewhere that increased autonomy will improve hospital performance. This article compares the performance of three private not-forprofit (PNFP) and public hospital pairs to address this question. PNFP and public hospitals have similar management structures but PNFP hospitals had better trained managers and a church affiliated chair in the hospital management committee. Both types have problems with personnel management but these appear more pronounced in public hospitals. Drug supply management appears better in PNFP hospitals. Overall, workloads are similar, but analysis of patterns of utilisation and prices across services suggest that patient choice of facilities is influenced by relative price levels, and that willingness to pay is higher for PNFP services. PNFP hospitals are more successful at generating revenue. There are no clear differences in efficiency between PNFP and public hospitals but there is some evidence of higher quality levels in PNFP hospitals. PNFP hospitals’ performance is plausibly related to three areas of managerial autonomy. First, better management of drug supply is facilitated by their freedom to purchase drugs from the open market. Second, greater success with personnel management is plausibly related to their greater autonomy over staffing. Third, higher levels of cost recovery are enabled by their freedom to set fees. However, differences in accountability and competence of hospital management, and population willingness to pay for services may also help to explain differences. Further, the use of PNFP financing strategy by public hospitals has implications for universal access to hospital services. Although there appear to be potential advantages from greater public hospital autonomy, the Ugandan government should ensure it has developed strategies to enhance public hospital management and to protect access to public hospitals before advancing further with hospital autonomy policy
Keywords: hospital autonomy; public hospital; PNFP HOSPITALS